Can unmixed complex forming polymer surfactant formulations be injected into oil reservoirs or aquifers without clogging them?. Issue 25 (7th June 2021) - Hamouma, Massinissa; Delbos, Aline; Dalmazzone, Christine; Colin, Annie
Abstract : In the context of enhanced oil recovery or soil remediation, we study the role of interactions between polymers and surfactants on the injectivity of formulations containing mixtures of polymers and surfactants. Abstract : In the context of enhanced oil recovery or soil remediation, we study the role of interactions between polymers and surfactants on the injectivity of formulations containing mixtures of polymers and surfactants. We show that contrary to the first intuition, the formation of aggregates in polymers surfactants formulations is not necessarily a hindrance to the injection of these formulations into pores. It is important above all to compare the size of aggregates according to the applied shear rate and the pore size to find the formulations that may induce clogging. We highlight a new positive and unexpected phenomenon. The small aggregates that do not lead to clogging ensure the transport of the surfactant vesicles in the porous medium and limit the adsorption of the latter.